1952
DOI: 10.1002/jsfa.2740030108
|View full text |Cite
|
Sign up to set email alerts
|

A mode of action of antibiotics in chick nutrition

Abstract: Procaine penicillin [penicillin (procaine salt)] added to a good practical ration improved the growth of chicks in a laboratory used for poultry for ten years. Chicks from the same batch in two other laboratories, where birds had not been kept before, grew equally well on the ration with and without penicillin, and growth was the same as that on the penicillinsupplemented diet in the usual chick laboratory. The growth depression in the absence of dietary penicillin was not due to differences in management or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

1952
1952
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(22 citation statements)
references
References 22 publications
3
18
1
Order By: Relevance
“…This is not in agreement with the data of Branion and Hill ((1952). However, in view of the reports by Coates et al, (1951Coates et al, ( , 1952; Bird et al, (1952);, regarding the influence of environment on the antibiotic response with chicks, it may well be that the disagreement between the results reported herein and those of Branion and Hill (1952) is due, in part at least, to the different environments encountered.…”
Section: Resultscontrasting
confidence: 78%
“…This is not in agreement with the data of Branion and Hill ((1952). However, in view of the reports by Coates et al, (1951Coates et al, ( , 1952; Bird et al, (1952);, regarding the influence of environment on the antibiotic response with chicks, it may well be that the disagreement between the results reported herein and those of Branion and Hill (1952) is due, in part at least, to the different environments encountered.…”
Section: Resultscontrasting
confidence: 78%
“…If one assumes the presence of a low-grade infection controllable by antibiotics (Sieburth et al, 1951;Coates et al, 1952;Hill el al., 1953;and Lillie et al, 1953) a response to antibiotic would persist no matter what strictly nutritional measures were attempted. Such was the case in our experiments from August 1950 to May 1952.…”
Section: Methodsmentioning
confidence: 99%
“…Roura et al (1992) showed that dietary antibiotics were effective at stimulating growth in the unsantitized environment, but not in the clean environment. Similarly, when new poultry facilities were built in the 1950s, it was noted that antibiotics were less effective at stimulating growth (Coates et al, 1952;Hill et al, 1952). Growth suppression resulting from increasing the chick density in a housing unit could be prevented through the feeding of antibiotics (Dafwang et al, 1987).…”
Section: Use Of Antibiotics As Growth Stimulantsmentioning
confidence: 97%